2015
DOI: 10.1136/acupmed-2014-010572
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Transcutaneous Electrical Acupuncture Point Stimulation on Endometrial Receptivity in Women Undergoing Frozen-Thawed Embryo Transfer: A Single-Blind Prospective Randomised Controlled Trial

Abstract: Objective To evaluate the effect of transcutaneous electrical acupuncture point stimulation (TEAS) on endometrial HOXA10 protein expression and three-dimensional (3D) power Doppler ultrasound parameters as markers of endometrial receptivity in women undergoing frozen-thawed embryo transfer (FET). Methods A total of 68 women undergoing FET were randomised to receive TEAS or mock TEAS at acupuncture points CV3, CV4 and SP6 and Zigong bilaterally. Both groups had six sessions per cycle for three menstrual cycles … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
81
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(82 citation statements)
references
References 32 publications
1
81
0
Order By: Relevance
“…In recent years, several articles have reported the positive role of TEAS in IVF [28][29][30], confirming our initial assumption and indicating that we should focus on comfort acupuncture for infertility, not like paralytic diseases, and the stronger the stimulation, the better the effect [31]. e patient should feel relaxed or unstressed and be adapted to the technique and acupuncturist before the IVF cycle begins.…”
Section: Future Directionssupporting
confidence: 74%
“…In recent years, several articles have reported the positive role of TEAS in IVF [28][29][30], confirming our initial assumption and indicating that we should focus on comfort acupuncture for infertility, not like paralytic diseases, and the stronger the stimulation, the better the effect [31]. e patient should feel relaxed or unstressed and be adapted to the technique and acupuncturist before the IVF cycle begins.…”
Section: Future Directionssupporting
confidence: 74%
“…The paper by Shuai et al 48 used TEAS rather than needle acupuncture and examined its efficacy and mechanisms of action in women undergoing frozen-thawed ET. TEAS significantly increased the clinical pregnancy rate (CPR) and LBR relative to a sham intervention (mock TEAS).…”
mentioning
confidence: 99%
“…Currently, studies have begun to explore whether acupuncture and moxibustion can improve endometrial receptivity. For example, Zheng et al [ 13 ] found that percutaneous acupoint electrical stimulation can improve endometrial receptivity, thus increasing the pregnancy rate of IVF-ET patients. Xing et al [ 14 ] found that combination of acupuncture and medicine can significantly improve endometrial receptivity of patients.…”
Section: Discussionmentioning
confidence: 99%